IMPROVING STUDENT ACHIEVEMENT IN WRITING NARRATIVE TEXT THROUGH APPLICATION OF THINK TALK WRITE STRATEGY - Siti Fitri Hasibuan; Saidatul Khairiyah; Sri Rahma Yani Harahap (Journal of Quality Islamic Education Research, 2024)
This study aimed to determine the improvement of students' writing achievement in narrative text using the think-talk-write Strategy at AL-HUSNA boarding school. The subject of this study was students of eight grade Madrasah tingkat stnawiyah Swasta Al-Husna Marindal. It consisted of 32 Students. The study's objective was to improve the students' achievement in writing Narrative text by using the think-talk-write Strategy. This study's research was conducted using the think-talk-write Strategy in Classroom Action Research. The technique of analyzing the data of this research is applied to qualitative and quantitative data. The qualitative data were taken from diary notes, interview sheets, observation sheets, and documentation. Based on the writing tests, the student's scores kept improving on every test, which could be seen from the improvement of students' mean scores from the pre-test, post-test of cycle I, and post-test of cycle II. The improvement can also be proved by the result of the observation sheet and diary notes, which showed the expression of the students. The quantitative data were taken from the writing test. In the pre-test, the students got up to 65. There were only 2 of 32 students (6,25%). In the post-test of cycle 1, students who got up to 65 were 8 of 32 (25%). It means that there was an improvement of about 18,75%. In the post-test of cycle II, students who got up to 65 were 29 of 32 (90,62%). The improvement was about 65,62%. The total improvement of the student's scores from the pre-test to the post-test of cycle II was 84,37%. In other words, the students got a better score at the next meeting. Based on the findings, the alternative hypothesis was accepted. This means that talking and writing could improve students' achievement in writing narrative text.